RANCANGAN SUMUR RESAPAN DI SUB DAS GARANG HILIR KOTA SEMARANG, JAWA TENGAH - , ARDIAN PERMATA PUTRA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Semarang City is a region with very rapid city development.The continuous growth of the population increasing landuse change, thus affecting the urban water system due to reduced water catchment areas. It is one of the cause of flooding in Semarang City. An effort is required to cope with this flood. Recharge well is one technique that can be used to address flooding problems. This study was carried out in Garang Hilir Sub-watershed which located in Semarang City administrative area. The purpose of this research is to design recharge well as a mean of groundwater conservation efforts to cope with flood by determining the design on the roofâs area. The study was employed with survey methods. The permeability was measured directly in the field using the inverse auger hole method. Roof area was determined by digitization on satellite imagery. Extreme rainfall estimation was calculated using log-Pearson type III distribution. Once the parameters are known, recharge wellâs depth was calculated with Sunjotoâs formula. The results showed that the estimated rainfall intensity with return period of 10 years and a duration of 1 hour in Garang Hilir Sub-watershed was 82.24 mm/hour. The permeability ranged from 0.35 to 2.66 m/day. Recharge well designâs depth ranged from 2.98 m to 5.54 m depends on the roof area. The recharge wellâs priority area are located in the administrative area of Semarang Barat District, Ngaliyan District and Gajah Mungkur District.